(untitled) (Damascus University Journal of agriculture sciences, 2021)
The study was carried out at one of the experimental fields of Al-Hanadi station which is affiliated to the Agricultural Scientific Research Station in Lattakia, in order to study the effect of the addition of zeolite ore with two different levels and the addition of sewage sludge to improve the chemical properties of sandy soil and study the interaction between zeolite ore and sewage sludge and their role in availability of some nutrients for plants. RCB Design has been used with three replicates for each treatment. The results showed that addition of zeolite ore and sewage sludge or both together have raised the cation exchange capacity of the soil compared to the treatment of mineral fertilization. The pH values of the treatment of sewage sludge added ​​were low in comparison to the other treatments. The available Phosphorus values ​​were increased in the sewage sludge treatments and the highest values were ​​in the treatment of sewage sludge then zeolite2+ sewage sludge, and zeolite1 + sewage sludge though differences among these treatments were not significant. The results clearly showed the role of zeolite ore and sewage sludge in increasing the available Potassium values. The differences between the values ​​were significant in the following order: zeolite 2+ sludge> zeolite 2> sludge> mineral fertilization with values ​​of 469.00, 345.67, 276.33, 168.67 and 96.00 ppm, respectively.